Case Report: COVID-19-Associated ROHHAD-Like Syndrome - Artamonova, Irina N.; Petrova, Natalia A.; Lyubimova, Natalia A.; Kolbina, Natalia Yu; Bryzzhin, Alexander V.; Borodin, Alexander V.; Levko, Tatyana A.; Mamaeva, Ekaterina A.; Pervunina, Tatiana M.; Vasichkina, Elena S.; Nikitina, Irina L.; Zlotina, Anna M.; et al. (Frontiers in Pediatrics, 2022)
It is known that the SARS-CoV-2 virus may cause neurologic damage. Rapid-onset obesity, hypoventilation, hypothalamus dysfunction, and autonomic dysregulation (ROHHAD) syndrome is a disease of unknown etiology with a progressive course and unclear outcomes. The etiology of ROHHAD syndrome includes genetic, epigenetic, paraneoplastic, and immune-mediated theories, but to our knowledge, viral-associated cases of the disease have not been described yet. Here we present the case of a 4-year-old girl who developed a ROHHAD syndrome-like phenotype after a COVID-19 infection and the results of 5 months of therapy. She had COVID-19 pneumonia, followed by electrolyte disturbances (hypernatremia and hyperchloremia), hypocorticism and hypothyroidism, central hypoventilation—requiring prolonged assisted lung ventilation—bulimia, and progressive obesity with hypertriglyceridemia, dyslipidemia, hyperuricemia, and hyperinsulinemia. The repeated MRI of the brain and hypothalamic–pituitary region with contrast enhancement showed mild post-hypoxic changes. Prader–Willi/Angelman syndrome as well as PHOX2B-associated variants was ruled out. Treatment with non-steroidal anti-inflammatory drugs and monthly courses of intravenous immunoglobulin led to a dramatic improvement. Herein the first description of ROHHAD-like syndrome is timely associated with a previous COVID-19 infection with possible primarily viral or immune-mediated hypothalamic involvement.